Health Law Reform In Indonesia: Challenges And Opportunities In Realizing Universal Health - Azhar. AR; Ismaidar, Ismaidar; Tamaulina Br. Sembiring (Jurnal EduHealth, 2024)
Health law reform in Indonesia is an important agenda in efforts to realize universal health that is fair and equitable for all levels of society. Along with social and economic developments, the Indonesian health system faces various challenges, such as unequal access to health services, unequal quality of services, and high financing burdens. Therefore, reforms in the health legal system are needed to increase the effectiveness and efficiency of health services, as well as ensuring the right of every citizen to receive adequate health services. This article discusses the main challenges in implementing health law reform in Indonesia, including unequal health infrastructure, limited human resources, and regulatory and bureaucratic obstacles. Apart from that, this article also explores existing opportunities, such as the use of digital technology, improving the National Health Insurance (JKN) system, and increasing community participation in decision making regarding health policy. Through analysis of various policies and experiences of other countries, it is hoped that recommendations can be obtained to improve Indonesia's health legal system in realizing universal health goals. With the right reforms, Indonesia can improve the quality of health services that are inclusive and accessible to all its citizens, without exception.